Incidence of Cerebrovascular Accidents Following Brain Tumor Surgery - Khomand, Payam; Moradi, Ghobad; Noorani poor, Voorya (International Clinical Neuroscience Journal, 2017)
Background and Purpose: Cancer and cerebrovascular accidents (CVA) are two most common causes of mortality and morbidity in the elderly. Patients with brain tumor can be highly affected by postsurgical stroke. CVA may be the first manifestation in these patients . Therefore, we aimed to assess the epidemiological factors affecting CVA after brain surgery. Methods: In this cross-sectional study we enrolled 241 patients admitted for brain surgery due to a brain tumor during April 2009 to March 2013 in Tohid Hospital, Sanandaj, Iran, using the convenient sampling method. Results: The mean±SD age of the patients was 48.1±21.3 years. 5 patients (2%) were complicated with CVAs(4ischemic stroke and one haemorrhagic). The frequency of CVA was not different regarding age,sex,type of tumor, tumor site,hypertension, diabetes mellitus, smoking, and type of intervention.Type of tumor was meningioma in 2 patients, Oligodendroglioma in 2 patients, and metastatic cancer in 1 patient. Of the 5 patients with CVA, 2 were in middle fossa (1.9% of middle fossa tumors), 2 in anterior fossa (2.5%), and one in the meningeal membrane (3.3%). Conclusion:Despit low incidence of stroke in this study,it seems there is a considerable rate of mortality and morbidity of cerebral vascular diseases, especially in people with underlying chronic medical conditions such as brain tumors necessitates regular follow-up of patients with brain tumors for assessing risk factors to be able to increase survival rate and reduce disease-related complications.